Ingredients of institutional reputations and citizen engagement with regulators. Issue 4 (17th August 2015) - Capelos, Tereza; Provost, Colin; Parouti, Maria; Barnett, Julie; Chenoweth, Jonathan; Fife‐Schaw, Chris; Kelay, Tanika
Abstract: The purpose of this study is to examine the link between the reputational components of efficacy and moral reliability of institutions, and citizens' compliance with institutional recommendations. Research on bureaucratic reputations highlights the significance of positive political reputations based on credibility and legitimacy, but the impact of these components is not systematically isolated and studied. We draw insights from political psychology to move beyond a positive‐negative valence‐based approach of reputation, and highlight the different effect of efficacy and moral reliability components of reputation on citizens' cooperation, engagement in water saving activities, and levels of complaints. We use the Cypriot Water Authority as a case study and inquire how its institutional reputation influences Cypriot citizens' behavior regarding water use. Our data was collected via a representative national survey administered to a random sample of 800 Cypriots in the spring of 2009 and show that favorable perceptions of particular components of institutional reputation shape the levels of satisfaction with specific organizational outputs.